Auxin Extraction and Purification Based on Recombinant Aux/IAA Proteins. Issue 1 (December 2017) - Su, Yi; Luo, Weigui; Chen, Xiaofei; Liu, Huizhen; Hu, Yueqing; Lin, Wanhuang; Xiao, Langtao
Abstract Background Indole-3-acetic acid (IAA) extraction and purification are of great importance in auxin research, which is a hot topic in the plant growth and development field. Solid-phase extraction (SPE) is frequently used for IAA extraction and purification. However, no IAA-specific SPE columns are commercially available at the moment. Therefore, the development of IAA-specific recognition materials and IAA extraction and purification methods will help researchers meet the need for more precise analytical methods for research on phytohormones. Results Since the AUXIN RESISTANT/INDOLE-3-ACETIC ACID INDUCIBLE (Aux/IAA) proteins show higher specific binding capability with auxin, recombinant IAA1, IAA7 and IAA28 proteins were used as sorbents to develop an IAA extraction and purification method. A GST tag was used to solidify the recombinant protein in a column. Aux/IAA proteins solidified in a column have successfully trapped trace IAA in aqueous solutions. The IAA7 protein showed higher IAA binding capability than the other proteins tested. In addition, expression of the IAA7 protein inDrosophila Schneider 2 (S2) cells produced better levels of binding than IAA7 expressed inE. coli . Conclusion This work validated the potential of Aux/IAA proteins to extract and purify IAA from crude plant extracts once we refined the techniques for these processes.